Critical gastrointestinal bleed due to secondary aortoenteric fistula - Mohammad U. Malik; Enver Ucbilek; Amanpreet S. Sherwal (Greater Baltimore Medical Center, 2015)
Secondary aortoenteric fistula (SAEF) is a rare yet lethal cause of gastrointestinal bleeding and occurs as a complication of an abdominal aortic aneurysm repair. Clinical presentation may vary from herald bleeding to overt sepsis and requires high index of suspicion and clinical judgment to establish diagnosis. Initial diagnostic tests may include computerized tomography scan and esophagogastroduodenoscopy. Each test has variable sensitivity and specificity. Maintaining the hemodynamic status, control of bleeding, removal of the infected graft, and infection control may improve clinical outcomes. This review entails the updated literature on diagnosis and management of SAEF. A literature search was conducted for articles published in English, on PubMed and Scopus using the following search terms: secondary, aortoenteric, aorto-enteric, aortoduodenal, aorto-duodenal, aortoesophageal, and aorto-esophageal. A combination of MeSH terms and Boolean operators were used to device search strategy. In addition, a bibliography of clinically relevant articles was searched to find additional articles (Appendix A). The aim of this review is to provide a comprehensive update on the diagnosis, management, and prognosis of SAEF.